Controlled Synthesis of Manganese Dioxide Nanostructures via a Facile Hydrothermal Route - Pang, Suh Cem; Chin, Suk Fun; Ling, Chian Ye (Hindawi Publishing Corporation, 2019)
Manganese dioxide nanostructures with controllable morphological structures and crystalline phases were synthesized via a facile hydrothermal route at low temperatures without using any templates or surfactants. Both the aging duration and aging temperatures were the main synthesis parameters used to influence and control the rate of morphological and structural evolution of MnO2 nanostructures. MnO2 nanostructures comprise of spherical nanoparticulate agglomerates and highly amorphous in nature were formed at lower temperature and/or short aging duration. In contrast, MnO2 nanostructures of sea-urchin-like and nanorods-like morphologies and nanocrystalline in nature were prepared at the combined higher aging temperatures and longer aging durations. These nanostructures underwent notable phase transformation from δ-MnO2 to α-MnO2 upon prolonged hydrothermal aging duration and exhibited accelerated rate of phase transformation at higher aging temperature.